2015
DOI: 10.1038/ncomms10191
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional elongation requires DNA break-induced signalling

Abstract: We have previously shown that RNA polymerase II (Pol II) pause release and transcriptional elongation involve phosphorylation of the factor TRIM28 by the DNA damage response (DDR) kinases ATM and DNA-PK. Here we report a significant role for DNA breaks and DDR signalling in the mechanisms of transcriptional elongation in stimulus-inducible genes in humans. Our data show the enrichment of TRIM28 and γH2AX on serum-induced genes and the important function of DNA-PK for Pol II pause release and transcriptional ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
275
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 188 publications
(291 citation statements)
references
References 58 publications
15
275
1
Order By: Relevance
“…2 It has been shown that some of the components of the NHEJ pathway such as DNA-dependent kinase (DNA-PK), Ku70 and Ku80 become associated with activated genes, including estrogen-induced genes, heat shock genes and serum-inducible immediate early (IE) genes. 4,6 The NHEJ intermediates were shown to be associated with ERinduced genes in a complex with Poly (ADP-Ribose) Polymerase 1 (PARP1), Topoisomerase IIb and transcription appeared to require Topoisomerase IIb-mediated nicking of sequences within the promoter of the presenilin 2 (pS2) gene 4 (Fig. 1).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…2 It has been shown that some of the components of the NHEJ pathway such as DNA-dependent kinase (DNA-PK), Ku70 and Ku80 become associated with activated genes, including estrogen-induced genes, heat shock genes and serum-inducible immediate early (IE) genes. 4,6 The NHEJ intermediates were shown to be associated with ERinduced genes in a complex with Poly (ADP-Ribose) Polymerase 1 (PARP1), Topoisomerase IIb and transcription appeared to require Topoisomerase IIb-mediated nicking of sequences within the promoter of the presenilin 2 (pS2) gene 4 (Fig. 1).…”
mentioning
confidence: 99%
“…Inducible gene transcription has been shown to be accompanied by the generation of DNA double strand breaks (DSB) in cells activated by agents as diverse as heat shock, growth serum, androgens, neuronal activation or estrogens. 1,[4][5][6][7] Increased DSB have been detected directly in transcribing cells, as well as indirectly by the Comet assay and by incorporation into chromatin of the histone gH2Ax, a surrogate marker of DNA damage. [5][6][7] Indeed direct generation of DSB in the promoters of the EGR1 and NPAS4 genes, using a CRISPR-CAS approach, was sufficient to drive transcription even in the absence of external stimuli.…”
mentioning
confidence: 99%
See 3 more Smart Citations